An atypical pneumococcal arthritis. (18th October 2010) - Rossi, Pascal; Granel, Brigitte; Mouly, Philippe; Demoux, Anne-Laurence; Le Mée, Fanny; Bernard, Fanny; Faugère, Gerard; Francès, Yves
Abstract : Bone and joint infections due to Streptococcus pneumoniae usually occur in patients who are immunocompromised, and involve one site. The unique case of a 49-year-old immunocompetent man, with an unremarkable medical history, with septicaemia and polyarticular septic arthritis involving the shoulder and knee and with cervical spondylodiscitis due to S pneumoniae, is described. In this case, S pneumoniae probably originated from the gingiva, which is commonly colonised in children and adults. S pneumoniae should be considered routinely when facing bone and joint infections, and multiple locations should be carefully sought owing to the possible lack of symptoms.